Precursor with porous structure and coating layer as well as preparation method and application of precursor
Through the use of porous structures and overwriting three -yuan front -drive body as the front -drive body of the positive electrode material, the problem of low lithium ion diffusion efficiency is solved, the higher charging and discharge efficiency and battery capacity maintenance rate is achieved, and the structure of the material is guaranteed stability.
Patent Information
- Application Number
- CN202411501363.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The cathode material of existing lithium-ion batteries has low diffusion efficiency of lithium ions during sintering, resulting in a decrease in charge and discharge efficiency and battery capacity retention rate.
The front -drive body with porous structure and cover layer is used. The core is a ternary front -driven body with a porous structure. stability.
It improves the diffusion efficiency of lithium ions, enhances the charging and discharge efficiency of the positive pole material and the battery capacity maintenance rate, while avoiding the structural collapse during the sintering process.
Smart Images

Figure CN119370916A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a precursor with a porous structure and a coating layer, and a preparation method and application thereof. Background Art
[0002] Lithium-ion battery is a new energy source with high energy density, high cycle performance and good stability. At present, in order to further improve the performance of lithium-ion batteries, doping modification and surface coating are simple and efficient means. CN117776294 A provides an aluminum-coated precursor and a preparation method thereof, comprising the following steps: (1) preparing a solution: preparing a metal salt solution of a certain concentration, wherein the metal salt is selected from at least one of nickel salt, cobalt salt and manganese salt; preparing an aluminum sulfate solution of a certain concentration and pH; preparing a complexing agent solution and a precipitant solution of a certain concentration; (2) preparing an uncoated precursor by co-precipitation reaction: introducing a metal salt solution, a precipitant solution and a complexing agent solution into a reactor containing a bottom liquid at the same time for a co-precipitation reaction, opening a concentrator to clear the reaction during the reaction process, keeping the liquid level in the reactor unchanged, and controlling the reaction conditions to be a first temperature, a first pH and a first stirring speed, and the reaction During the process, a protective atmosphere is introduced, and the introduction of the metal salt solution is stopped after the reaction reaches the target particle size, thereby obtaining an uncoated precursor; (3) aluminum coating: the conditions of the reactor are adjusted to the second temperature and the second stirring speed, and the aluminum sulfate solution of step (1) is introduced into the reactor at a lower flow rate. The pH in the reactor decreases with the addition of the aluminum sulfate solution, and is maintained constant after decreasing to the target second pH. After sufficient aluminum sulfate solution is introduced, the introduction of the aluminum sulfate solution is stopped, and stirring is continued for a certain period of time; (4) post-treatment: sodium carbonate is added to the reactor, and the temperature of the reactor is increased at the same time. After stirring for a certain period of time, the aluminum-coated Ni is obtained by post-treatment. x Co y Mn z (OH)2 spherical precursor particles, where x+y+z=1, and 0≤x≤1, 0≤y≤1, 0≤z≤1. This method has a good coating effect, but since the metal liquid is not introduced in parallel when the aluminum liquid is introduced, small particles are easily exploded when the aluminum layer is coated. This phenomenon is particularly obvious when the particle size is high, and the coating layer is thin, which has little effect on the stability of the positive electrode material.
[0003] At the same time, neither the doping nor the coating method can effectively increase the specific surface area of the precursor, thereby failing to effectively improve the diffusion efficiency of lithium ions during the sintering process of the positive electrode material. It will also lead to a decrease in the contact area between the positive electrode material and the electrolyte, thereby reducing the battery's charge and discharge efficiency and battery capacity retention rate.
[0004] Therefore, providing a precursor to effectively improve the diffusion efficiency of lithium ions during the sintering process, improve the battery's charge and discharge efficiency and battery capacity retention rate is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the above problems existing in the prior art, the object of the present invention is to provide a precursor having a porous structure and a coating layer, and a preparation method and application thereof.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a precursor having a porous structure and a coating layer, characterized in that the precursor comprises an inner core and at least one coating layer, the inner core is a ternary precursor having a porous structure, and the outermost layer of the coating layer is an aluminum-doped ternary precursor.
[0008] The interior of the precursor provided by the present invention has a porous structure. This loose structure is conducive to increasing the specific surface area of the precursor and improving the diffusion efficiency of lithium ions during the sintering process. The positive electrode material prepared using the precursor inherits the porous structure, which is conducive to the release and embedding of lithium ions, and is conducive to improving the charging and discharging efficiency of the battery and the battery capacity retention rate. At the same time, since the outermost side is coated with an aluminum-doped ternary precursor, the structure of the precursor can be effectively stabilized, avoiding collapse and crushing during mixed lithium sintering, and ensuring good electrochemical properties of the material.
[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0010] Preferably, the chemical formula of the porous structure part of the core is Ni x Co y Mn z (OH)2, where 0 <x<1,0<y<1,0<z<1,x+y+z=1。
[0011] Preferably, the chemical formula of the aluminum-doped ternary precursor is Ni a Co b Mn c Al d (OH) 2(a+b+c)+3d , where 0 <a<1,0<b<1,0<c<1,0<d<1,a+b+c+d=1。
[0012] Preferably, the particle size D50 of the inner core is 3-6 μm, for example, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm.
[0013] Preferably, the thickness of the outermost layer is 0.5-2 μm, for example, 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.3 μm, 1.5 μm, 1.7 μm or 2 μm.
[0014] Preferably, the coating layer further includes an intermediate layer, and the intermediate layer includes at least one group of aluminum-doped ternary precursor layers and porous structure layers that are sequentially adjacent from the inside to the outside.
[0015] Preferably, the chemical formula of the porous structure layer in the intermediate layer is Ni x Co y Mn z (OH)2, where 0 <x<1,0<y<1,0<z<1,x+y+z=1。
[0016] Preferably, the thickness of the porous structure layer in the middle layer is 3-6 μm, for example, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm.
[0017] Preferably, the chemical formula of the aluminum-doped ternary precursor layer in the intermediate layer is Ni a Co b Mn c Al d (OH) 2(a+b+c)+3d , where 0 <a<1,0<b<1,0<c<1,0<d<1,a+b+c+d=1;
[0018] Preferably, the thickness of the aluminum-doped ternary precursor layer in the intermediate layer is 0.5-2 μm, for example, 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.3 μm, 1.5 μm, 1.7 μm or 2 μm.
[0019] In a second aspect, the present invention provides a method for preparing a precursor having a porous structure and a coating layer as described in the first aspect, the method comprising the following steps:
[0020] (1) introducing a ternary metal salt solution, a precipitant solution, a complexing agent solution, and a zinc salt solution into a reaction kettle containing a base solution, and performing a coprecipitation reaction until the inner core has a predetermined particle size, stopping the reaction, and adjusting the pH to dissolve zinc to obtain an inner core having a porous structure;
[0021] (2) A ternary metal salt solution and an aluminum salt solution are introduced into the reactor to continue the coprecipitation reaction, and an aluminum-doped ternary precursor layer is coprecipitated and grown on the surface of the inner core of the porous structure to obtain a precursor having a porous structure and a coating layer.
[0022] In the method of the present invention, it should be noted that zinc needs to be dissolved out before coating the aluminum-doped ternary precursor layer. If the zinc dissolution step is performed after coating the aluminum-doped ternary precursor layer, it will make it difficult for the zinc element to dissolve out.
[0023] The method of the present invention utilizes the precipitation and dissolution of zinc elements to form pores, which can ensure that the small pores are evenly distributed in the loose porous structure, which is beneficial to improving the diffusion efficiency of lithium ions during the sintering process on the one hand, and can make the pore structure of the positive electrode material prepared by using the method evenly distributed on the other hand, which is beneficial to the release and embedding of lithium ions and improves the electrochemical performance of the battery. Furthermore, in the method of the present invention, the aluminum-doped ternary precursor layer is coated on the outside by the coprecipitation method, and its structural preparation can effectively stabilize the structure of the material.
[0024] The precursor prepared by the method of the present invention has good structural stability while maintaining a high specific surface area. The positive electrode material prepared by the precursor inherits a good porous structure and avoids the problem of structural collapse during sintering.
[0025] In the method of the present invention, the density of the pores in the porous structure can be adjusted by adjusting the feeding amount of the zinc salt solution.
[0026] The present invention does not limit the preparation method of the ternary metal salt solution. For example, the ternary metal salt may be dissolved in water to obtain the ternary metal salt solution.
[0027] By way of example and not limitation, the ternary metal salts are nickel salts, cobalt salts and manganese salts.
[0028] In the present invention, the nickel salt, cobalt salt and manganese salt are independently selected from at least one of sulfate, nitrate and chloride. "Independently" means that the nickel salt, cobalt salt and manganese salt are selected independently and do not affect each other.
[0029] The present invention does not specifically limit the types of the precipitant solution and the complexing agent solution. Exemplarily, the precipitant solution is a sodium hydroxide solution, and the complexing agent solution is an ammonia solution.
[0030] Preferably, the ternary metal salt solution in step (1) is a nickel-cobalt-manganese ternary metal salt solution.
[0031] Preferably, the base liquid comprises water, a precipitant and a complexing agent.
[0032] Preferably, the pH of the base solution is 9-12, for example, it can be 9, 9.2, 9.5, 9.8, 10, 10.3, 10.5, 10.8, 11, 11.2, 11.5, 11.8 or 12, etc.
[0033] Preferably, the ammonia concentration in the base liquid is 4-10 g / L, for example, it can be 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L or 10 g / L, etc.
[0034] In one embodiment, the bottom liquid occupies 1 / 3 to 2 / 3 of the volume of the reactor.
[0035] In one embodiment, the preparation method is carried out under a protective atmosphere.
[0036] Preferably, the concentration of the ternary metal salt solution in step (1) is 90 g / L-110 g / L, for example, it can be 90 g / L, 95 g / L, 100 g / L, 105 g / L or 110 g / L.
[0037] Preferably, the concentration of the zinc salt solution in step (1) is 30-70 g / L, for example, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L or 70 g / L.
[0038] In the present invention, the zinc salt in the zinc salt solution includes but is not limited to at least one of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate.
[0039] Preferably, in step (1), the ratio of the feed rates of the ternary metal salt solution and the zinc salt solution is 10:(0.1-1), for example, it can be 10:0.1, 10:0.2, 10:0.3, 10:0.4, 10:0.5, 10:0.6, 10:0.7, 10:0.8, 10:0.9 or 10:1, etc.
[0040] Preferably, the pH of the coprecipitation reaction in step (1) is between 8 and 12, for example, it can be 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5 or 12, etc.
[0041] Preferably, during the coprecipitation reaction in step (1), the ammonia concentration in the reaction system is 4-10 g / L, for example, 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L or 10 g / L, etc.
[0042] Preferably, the temperature of the coprecipitation reaction in step (1) is 50-70°C, for example, 50°C, 55°C, 60°C, 65°C or 70°C.
[0043] Preferably, the pH of step (1) is adjusted by discharging the supernatant and introducing a precipitant solution to adjust the pH to 12-14 (for example, 12, 12.2, 12.4, 12.6, 12.8, 13, 13.2, 13.5, 13.7, 13.8 or 14, etc.) to dissolve zinc.
[0044] Preferably, in step (1), after zinc is dissolved, the inner core having a porous structure is rinsed and put back into the reactor.
[0045] As a preferred technical solution of the preparation method of the present invention, during the coprecipitation reaction in step (2), a complexing agent solution and a precipitant solution are also passed.
[0046] Preferably, during the coprecipitation reaction in step (2), the pH is maintained between 8 and 12, for example, 8, 8.3, 8.5, 8.6, 8.8, 9, 9.5, 10, 10.5, 11, 11.5 or 12. In the present invention, the pH can be maintained within this range by adjusting the amount of the precipitant solution and the complexing agent solution introduced.
[0047] Preferably, during the coprecipitation reaction in step (2), the ammonia concentration in the reaction system is between 4-8 g / L, for example, it can be 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, or 8 g / L.
[0048] Preferably, the temperature of the coprecipitation reaction in step (2) is 50-70°C, for example, 50°C, 55°C, 60°C, 65°C or 70°C.
[0049] Preferably, the concentration of the ternary metal salt solution in step (2) is 90 g / L-110 g / L, for example, it can be 90 g / L, 95 g / L, 100 g / L, 105 g / L or 110 g / L.
[0050] Preferably, the concentration of the aluminum salt solution in step (2) is 30 g / L-70 g / L, for example, it can be 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L or 70 g / L.
[0051] In the present invention, the aluminum salt in the aluminum salt solution includes but is not limited to at least one of aluminum sulfate and aluminum nitrate.
[0052] Preferably, in step (2), the ratio of the feed rates of the ternary metal salt solution and the aluminum salt solution is 10:(0.1-2), for example, it can be 10:0.1, 10:0.2, 10:0.3, 10:0.4, 10:0.5, 10:0.6, 10:0.7, 10:0.8, 10:0.9, 10:1, 10:1.2, 10:1.3, 10:1.5, 10:1.6, 10:1.7, 10:1.8, 10:1.9 or 10:2, etc.
[0053] As a preferred technical solution of the preparation method of the present invention, the preparation method further comprises, after obtaining the precursor having a porous structure and a coating layer, repeating step (1) and step (2) performed sequentially at least once.
[0054] In the precursor prepared by this preferred technical solution, the loose porous structure layer and the dense layer of the aluminum-doped precursor appear alternately, so that the precursor is not easy to break during the preparation process, especially for the precursor with a larger particle size, the precursor is not easy to break during the preparation process, which can reduce the difficulty of preparation. Moreover, the precursor prepared by this method has good stability while maintaining a high specific surface area, ensuring that it is not easy to break and collapse during the sintering process to prepare the positive electrode material.
[0055] In a third aspect, the present invention provides a positive electrode material, which is prepared using the precursor having a porous structure and a coating layer as described in the first aspect.
[0056] In a fourth aspect, the present invention provides a battery, comprising the positive electrode material described in the third aspect.
[0057] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] The interior of the precursor provided by the present invention has a porous structure. This loose structure is conducive to increasing the specific surface area of the precursor and improving the diffusion efficiency of lithium ions during the sintering process. The positive electrode material prepared using the precursor inherits the porous structure, which is conducive to the release and embedding of lithium ions, and is conducive to improving the charging and discharging efficiency of the battery and the battery capacity retention rate. At the same time, since the outermost side is coated with an aluminum-doped ternary precursor, the structure of the precursor can be effectively stabilized, avoiding collapse and crushing during mixed lithium sintering, and ensuring good electrochemical properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1is a SEM image of the precursor having a porous structure and a coating layer in Example 1. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0062] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0063] Example 1
[0064] This embodiment provides a precursor having a porous structure and a coating layer, and its scanning diagram is shown in Figure 1 The precursor includes a core 1 and at least one coating layer, the core 1 is a ternary precursor (nickel cobalt manganese hydroxide) with a porous structure, and the coating layers are, from the inside to the outside, an aluminum-doped ternary precursor layer 21 (nickel cobalt manganese aluminum hydroxide, thickness 1 μm), a porous structure layer 22 (nickel cobalt manganese hydroxide, thickness 3 μm) and an aluminum-doped ternary precursor layer 23 (nickel cobalt manganese aluminum hydroxide, thickness 1 μm).
[0065] This embodiment also provides a method for preparing the above-mentioned precursor having a porous structure and a coating layer, comprising the following steps:
[0066] (1) Prepare the raw material liquid for standby use:
[0067] A nickel-cobalt-manganese ternary metal salt solution is prepared, wherein nickel, cobalt and manganese are all derived from sulfate;
[0068] Dissolve zinc sulfate in pure water to prepare a zinc salt solution with a concentration of 50g / L;
[0069] Preparing a precipitant solution and a complexing agent solution of a certain concentration;
[0070] Dissolve aluminum sulfate in pure water to prepare an aluminum salt solution of a certain concentration.
[0071] (2) Coprecipitation preparation:
[0072] Pure water is introduced into the reactor, and then a precipitant and a complexing agent are introduced to prepare a bottom liquid, which accounts for 2 / 3 of the volume of the reactor. The pH of the bottom liquid is ensured to be 11.6, the ammonia concentration is 8 g / L, and the temperature is 60°C. A protective atmosphere (Ar) is introduced, and then a ternary metal salt solution, a precipitant solution, a complexing agent solution, and a zinc salt solution are introduced into the reactor to perform a coprecipitation reaction (during the reaction, the pH of the system is between 11.4 and 11.8, the ammonia concentration is between 6 and 8 g / L, and the temperature is 60°C). When the particle size reaches 3 μm, the reaction is suspended, the material is discharged through a thickener to remove the supernatant, and pure water and a precipitant solution are introduced again to adjust the pH to 11.6 to dissolve zinc, thereby obtaining an inner core with a porous structure. Finally, the supernatant is discharged, the product is washed with water, and then put back into the reactor. Pure water, precipitant solution, and complexing agent solution are introduced again to adjust the pH and ammonia concentration. The pH is 11.6 and the ammonia concentration is 8 g / L. Then, the ternary metal salt solution and the aluminum salt solution are introduced to continue the co-precipitation reaction (during the reaction, the pH of the system is between 11.4-11.8, the ammonia concentration is between 6-8 g / L, and the temperature is 60°C). A 1 μm dense aluminum-doped ternary precursor layer is grown. After the growth of the aluminum-doped dense layer is completed, a 3 μm porous structure layer is grown in the same way, and then a 1 μm dense aluminum-doped ternary precursor layer is grown again, and finally a precursor with a porous structure and a coating layer with a particle size of 8 μm is obtained.
[0073] Example 2
[0074] The present embodiment provides a precursor having a porous structure and a coating layer, the precursor comprising an inner core and at least one coating layer, the inner core being a ternary precursor (nickel, cobalt, manganese hydroxide) having a porous structure, the coating layer being, from the inside to the outside, an aluminum-doped ternary precursor layer (nickel, cobalt, manganese, aluminum hydroxide, 0.5 μm thick), a porous structure layer (nickel, cobalt, manganese, hydroxide, 3 μm thick), and an aluminum-doped ternary precursor layer (nickel, cobalt, manganese, aluminum hydroxide, 1.5 μm thick).
[0075] This embodiment also provides a method for preparing the above-mentioned precursor having a porous structure and a coating layer, comprising the following steps:
[0076] (1) Prepare the raw material solution for use. Nickel, cobalt and manganese are all derived from nitrates:
[0077] A nickel-cobalt-manganese ternary metal salt solution is prepared;
[0078] Dissolve zinc sulfate in pure water to prepare a zinc salt solution with a concentration of 40g / L;
[0079] Preparing a precipitant solution and a complexing agent solution of a certain concentration;
[0080] Dissolve aluminum sulfate in pure water to prepare an aluminum salt solution of a certain concentration.
[0081] (2) Coprecipitation preparation:
[0082] Pure water is introduced into the reactor, and then a precipitant and a complexing agent are introduced to prepare a base liquid, which occupies 1 / 3 of the volume of the reactor. The pH of the base liquid is ensured to be 12, and the ammonia concentration is 4 g / L. A protective atmosphere (He) is introduced, and then a ternary metal salt solution, a precipitant solution, a complexing agent solution, and a zinc salt solution are introduced into the reactor to carry out a coprecipitation reaction. When the particle size reaches 5 μm, the reaction is suspended, the material is discharged through a thickener, and the supernatant is removed. Pure water and a precipitant solution are introduced again, and the pH is adjusted to 14 to dissolve zinc to obtain an inner core with a porous structure. Then, the same The supernatant is drained, the product is washed with water and then put back into the reactor. Pure water, precipitant solution and complexing agent solution are introduced again to adjust the pH and ammonia concentration to 12 and 4 g / L, and then the ternary metal salt solution and aluminum salt solution are introduced to continue the co-precipitation reaction to grow a 0.5 μm dense aluminum-doped ternary precursor layer. After the growth of the aluminum-doped dense layer is completed, a 3 μm porous structure layer is grown in the same way, and then a 1.5 μm dense aluminum-doped ternary precursor layer is grown again to finally obtain a precursor with a porous structure and a coating layer.
[0083] Example 3
[0084] The present embodiment provides a precursor having a porous structure and a coating layer, wherein the precursor includes a core and at least one coating layer, wherein the core is a ternary precursor (nickel, cobalt, manganese hydroxide) having a porous structure, and the coating layer is, from the inside to the outside, an aluminum-doped ternary precursor layer (nickel, cobalt, manganese, aluminum hydroxide, with a thickness of 0.5 μm), a porous structure layer (nickel, cobalt, manganese, hydroxide, with a thickness of 4 μm), and an aluminum-doped ternary precursor layer (nickel, cobalt, manganese, aluminum hydroxide, with a thickness of 0.5 μm).
[0085] This embodiment also provides a method for preparing the above-mentioned precursor having a porous structure and a coating layer, comprising the following steps:
[0086] (1) Prepare the raw material liquid for standby use:
[0087] A nickel-cobalt-manganese ternary metal salt solution is prepared;
[0088] Dissolve zinc sulfate in pure water to prepare a zinc salt solution with a concentration of 60g / L;
[0089] Preparing a precipitant solution and a complexing agent solution of a certain concentration;
[0090] Dissolve aluminum sulfate in pure water to prepare an aluminum salt solution of a certain concentration.
[0091] (2) Coprecipitation preparation:
[0092] Pure water is introduced into the reactor, and then a precipitant and a complexing agent are introduced to prepare a base liquid, which occupies 2 / 3 of the volume of the reactor. The pH of the base liquid is ensured to be 10, and the ammonia concentration is 10g / L. A protective atmosphere (Ar) is introduced, and then a ternary metal salt solution, a precipitant solution, a complexing agent solution, and a zinc salt solution are introduced into the reactor to carry out a coprecipitation reaction. When the particle size reaches 3μm, the reaction is suspended, the material is discharged through a thickener to remove the supernatant, and pure water and a precipitant solution are introduced again, and the pH is adjusted to 13 to dissolve zinc to obtain an inner core with a porous structure, and then the same The supernatant is drained, the product is washed with water and then put back into the reactor. Pure water, precipitant solution and complexing agent solution are introduced again to adjust the pH and ammonia concentration to 10 and 10 g / L respectively. Then, the ternary metal salt solution and the aluminum salt solution are introduced to continue the co-precipitation reaction to grow a 0.5 μm dense aluminum-doped ternary precursor layer. After the growth of the aluminum-doped dense layer is completed, a 4 μm porous structure layer is grown in the same way, and then a 0.5 μm dense aluminum-doped ternary precursor layer is grown again to finally obtain a precursor with a porous structure and a coating layer.
[0093] Example 4
[0094] The difference between this embodiment and embodiment 1 is that the coating layer of the precursor is an aluminum-doped ternary precursor layer (nickel-cobalt-manganese-aluminum hydroxide, with a thickness of 1 μm).
[0095] Example 5
[0096] The difference between this embodiment and embodiment 1 is that the zinc salt solution is 20 g / L.
[0097] Example 6
[0098] The difference between this embodiment and embodiment 1 is that the zinc salt solution is 100 g / L.
[0099] Example 7
[0100] The difference between this embodiment and embodiment 1 is that the thickness of the dense aluminum-doped ternary precursor layer on the innermost side of the coating layer is 0.1 μm.
[0101] Example 8
[0102] The difference between this embodiment and embodiment 1 is that the thickness of the dense aluminum-doped ternary precursor layer on the innermost side of the coating layer is 3 μm.
[0103] Comparative Example 1
[0104] The difference between this comparative example and Example 1 is that the precursor does not contain a coating layer.
[0105] Comparative Example 2
[0106] The difference between this comparative example and Example 1 is that zinc is not dissolved out in the preparation method, and therefore, the precursor does not have a porous structure.
[0107] The positive electrode material obtained by sintering the precursor is used to prepare the positive electrode plate: the obtained positive electrode material, conductive carbon black SP (TIMCAL) and polyvinylidene fluoride PVDF (HSV900) are mixed in a mass ratio of 90:5:5, and N-methylpyrrolidone is used as a solvent. The mixture is mixed and stirred into a slurry, and the obtained slurry is evenly coated on an aluminum foil with a scraper with a coating gap of 100um; after coating, it is first blown dry, and then rolled and cut into circular electrode plates, and then vacuum dried at 120°C and the weight of the electrode plates is weighed to obtain a button half-cell positive electrode plate; a metal lithium plate is used as the negative electrode, a PP microporous membrane is used as the separator, and a lithium battery basic electrolyte is used as the electrolyte. The positive electrode plate, the metal lithium plate, the separator and the electrolyte are assembled to obtain a button battery;
[0108] The obtained battery was subjected to stability test and charge-discharge efficiency test. The method of the stability test is as follows: the capacity retention rate of the battery after 100 cycles at 25°C and the charge-discharge efficiency are shown in Table 1.
[0109] Table 1
[0110]
[0111]
[0112] As can be seen from Table 1, the interior of the precursor provided by the present invention has a porous structure. This loose structure is conducive to increasing the specific surface area of the precursor and improving the diffusion efficiency of lithium ions during the sintering process. The positive electrode material prepared using the precursor inherits the porous structure, which is conducive to the release and embedding of lithium ions, and is conducive to improving the charge and discharge efficiency of the battery and the battery capacity retention rate. At the same time, since the outermost side is coated with an aluminum-doped ternary precursor, the structure of the precursor can be effectively stabilized, avoiding collapse and crushing during mixed lithium sintering, and ensuring good electrochemical properties of the material.
[0113] At the same time, through the comparison between Example 1 and Example 4, it can be seen that the alternating arrangement of multiple layers of porous structure layers and aluminum-doped dense layers is beneficial to alleviating the internal collapse of the precursor during the sintering process, thereby improving the battery charge and discharge efficiency and cycle stability.
[0114] By comparing Example 1 with Examples 5-6, it can be seen that when the zinc concentration is too low, the internal pores of the precursor are not obvious; when the zinc concentration is too high, there are too many internal pores and the precursor is prone to collapse during sintering. Both situations are not conducive to improving battery performance.
[0115] By comparing Example 1 with Examples 7-8, it can be seen that the aluminum-doped dense layer is too thin and cannot prevent the loose porous layer from collapsing and breaking. The aluminum-doped dense layer is too thick, and the volume of the loose porous layer accounts for a relatively small proportion, and the battery performance improvement is not obvious.
[0116] By comparing Example 1 with Comparative Examples 1-2, it can be seen that the precursor does not have an outermost aluminum-doped dense layer. During the mixing and sintering process, the surface of the precursor collapses and is severely damaged, which directly reduces the stability of the positive electrode. The precursor does not have a loose porous structure, and lithium ion embedding and extraction are relatively difficult, and the battery capacity retention rate and charge and discharge efficiency are significantly reduced.
[0117] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A precursor having a porous structure and a coating layer, characterized in that: The precursor comprises a core and at least one coating layer, wherein the core is a ternary precursor with a porous structure, and the outermost layer of the coating layer is an aluminum-doped ternary precursor.
2. The precursor having a porous structure and a coating layer according to claim 1, characterized in that: The chemical formula of the porous structure of the core is Ni x Co y Mn z (OH)2, where 0 <x<1,0<y<1,0<z<1,x+y+z=1; Preferably, the chemical formula of the aluminum-doped ternary precursor is Ni a Co b Mn c Al d (OH) 2(a+b+c)+3d , where 0 <a<1,0<b<1,0<c<1,0<d<1,a+b+c+d=1; Preferably, the particle size D50 of the core is 3-6 μm; Preferably, the thickness of the outermost layer is 0.5-2 μm.
3. The precursor having a porous structure and a coating layer according to claim 1 or 2, characterized in that: The coating layer also includes an intermediate layer, and the intermediate layer includes at least one group of aluminum-doped ternary precursor layers and porous structure layers that are sequentially adjacent from the inside to the outside; Preferably, the chemical formula of the porous structure layer in the intermediate layer is Ni x Co y Mn z (OH)2, where 0 <x<1,0<y<1,0<z<1,x+y+z=1; Preferably, the thickness of the porous structure layer in the intermediate layer is 3-6 μm; Preferably, the chemical formula of the aluminum-doped ternary precursor layer in the intermediate layer is Ni a Co b Mn c Al d (OH) 2(a+b+c)+3d , where 0 <a<1,0<b<1,0<c<1,0<d<1,a+b+c+d=1; Preferably, the thickness of the aluminum-doped ternary precursor layer in the intermediate layer is 0.5-2 μm.
4. A method for preparing a precursor having a porous structure and a coating layer as claimed in any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) introducing a ternary metal salt solution, a precipitant solution, a complexing agent solution, and a zinc salt solution into a reaction kettle containing a base solution, and performing a coprecipitation reaction until the inner core has a predetermined particle size, stopping the reaction, and adjusting the pH to dissolve zinc to obtain an inner core having a porous structure; (2) A ternary metal salt solution and an aluminum salt solution are introduced into the reactor to continue the coprecipitation reaction, and an aluminum-doped ternary precursor layer is coprecipitated and grown on the surface of the inner core of the porous structure to obtain a precursor having a porous structure and a coating layer.
5. The preparation method according to claim 4, characterized in that: The ternary metal salt solution in step (1) is a nickel-cobalt-manganese ternary metal salt solution; Preferably, the base liquid comprises water, a precipitant and a complexing agent; Preferably, the pH of the base solution is 9-12; Preferably, the ammonia concentration in the base solution is 4-10 g / L; Preferably, the concentration of the ternary metal salt solution in step (1) is 90 g / L-110 g / L; Preferably, the concentration of the zinc salt solution in step (1) is 30-70 g / L; Preferably, in step (1), the ratio of the feed rate of the ternary metal salt solution to the zinc salt solution is 10:(0.1-1); Preferably, the pH of the coprecipitation reaction in step (1) is between 8 and 12; Preferably, during the coprecipitation reaction in step (1), the ammonia concentration in the reaction system is 4-10 g / L; Preferably, the temperature of the coprecipitation reaction in step (1) is 50-70°C.
6. The preparation method according to claim 4 or 5, characterized in that: The method of adjusting the pH in step (1) is: draining the supernatant and introducing a precipitant solution to adjust the pH to 12-14 to dissolve zinc; Preferably, in step (1), after zinc is dissolved, the inner core having a porous structure is rinsed and put back into the reactor.
7. The preparation method according to any one of claims 4 to 6, characterized in that: During the coprecipitation reaction in step (2), a complexing agent solution and a precipitant solution are also passed; Preferably, during the coprecipitation reaction in step (2), the pH is maintained between 8 and 12; Preferably, during the coprecipitation reaction in step (2), the ammonia concentration in the reaction system is between 4-8 g / L; Preferably, the temperature of the coprecipitation reaction in step (2) is 50-70°C; Preferably, the concentration of the ternary metal salt solution in step (2) is 90 g / L-110 g / L; Preferably, the concentration of the aluminum salt solution in step (2) is 30 g / L-70 g / L; Preferably, in step (2), the ratio of the feed rates of the ternary metal salt solution and the aluminum salt solution is 10:(0.1-2).
8. The preparation method according to any one of claims 4 to 7, characterized in that: The preparation method further comprises, after obtaining the precursor having a porous structure and a coating layer, repeating step (1) and step (2) performed sequentially at least once.
9. A positive electrode material, characterized in that: The positive electrode material is prepared by using the precursor having a porous structure and a coating layer as described in any one of claims 1 to 3.
10. A battery, characterized in that: The battery comprises the positive electrode material according to claim 9.
Citation Information
Patent Citations
Preparation method of aluminum-coated precursor
CN117776294A
Cited By
Ternary material precursor, preparation method thereof, ternary positive electrode material and battery
CN121470569A